STRATEGI KOMUNIKASI PENGUSAHA PASAR BARU TRADE CENTRE BANDUNG DALAM MENGHADAPI MARAKNYA PENGUSAHA UMKM ONLINE - Suci Kirani Putri; Kirana Widyadhana Rachman; M. Afrizal Maulana (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2022)
Technology is developing rapidly and has entered the 4.0 revolution era, one of the effects of this era is the buying and selling process. Many large and small entrepreneurs (SMEs) currently use two systems in their business activities, namely offline and online. The purpose of this study was to find out the communication strategies used by MSMEs during the rise of online shops. This type of research uses a qualitative-descriptive approach. The data collection technique used was interviews with 4 (four) SMEs at Pasar Baru Trade Center Bandung. The results of the study showed that the communication strategy used by MSMEs in Pasar Baru Trade Center Bandung were personal selling and direct marketing and pays attention to the 7P marketing mix elements. Entrepreneurs currently are experiencing a decline because of the large number of online entrepreneurs and the communication strategies used only promote directly. It is better for MSME actors to start adapting to current technological developments and pay attention to the communication strategies used.